MANAJEMEN BENCANA BANJIR DI KECAMATAN PANGEAN KABUPATEN KUANTAN SINGINGI - Febryanti; Geovani Meiwanda (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, 2022)
Pangean District is one of the sub-districts affected by flooding in Kuantan Singingi Regency. So that good flood disaster management is needed in order to reduce or minimize the risk caused by flood disasters. This study focuses on disaster management carried out by the Kuantan Singingi Regency Government, whether it is in accordance with the stages of disaster management, namely Pre-disaster, Emergency Response, and Post-disaster. so that this study is to find out how disaster management is carried out by the Kuantan Singingi Regency Government in tackling flood disasters. the theory used in this study is the theory of Ramli (2010:31) disaster management. There are three stages in managing a disaster, first there is a pre-disaster stage, the second is emergency response and the third is post-disaster. The research method used in this research is descriptive type qualitative method. The results of this study indicate that the stages of disaster management carried out by the Kuantan Singingi district government are starting from the pre-disaster where there are still shortcomings. When doing socialization, many people do not get this information. Then when a disaster occurs, there are shortages, namely logistical limitations and also disaster emergency personnel, and the last stage, namely post-disaster, there are still shortages where the form of rehabilitation carried out by the government is still not well targeted and lacks funds.